Serum HMGB1 levels and its clinical significance in elderly patients with intertrochanteric fractures after intramedullary fixation surgery. Issue 8 (22nd February 2023) - Zhao, Ling; Li, Haoran; Zhang, Shaohui; Dong, Zhanyin; Cui, Qing
Abstract : Background: Intramedullary fixation is a valuable alternative for the treatment of intertrochanteric fractures. However, further development of new biomarkers to predict the prognosis of the patient is still needed for timely and effective treatment and intervention. The present study aimed to explore the serum high-mobility group box 1 (HMGB1) levels in the prognosis of intertrochanteric fracture patients and its correlation with clinical results. Methods: The present prospective cohort study recruited 115 intertrochanteric fracture patients who were admitted from January 2015 to December 2019. All patients were evaluated preoperatively and treated (proximal femoral nail antirotation or intramedullary proximal femoral nail) by the same team. The serum HMGB1, interleukin-6, interleukin-1β, tumor necrosis factor α, and C-reactive protein levels were measured by enzyme-linked immunosorbent assay. Demographic and clinical data of all patients were collected. Harris score was used to assess the prognosis of intertrochanteric fracture patients after 6 months of treatment. Statistical analysis was conducted using SPSS software with P < .05 as statistically different. Results: The time of the operation and the amount of bleeding in intramedullary proximal femoral nail were remarkably elevated compared with the proximal femoral nail antirotation group ( P < .05). The age, proportion of complications and visual analogue score VAS after 72 hours of surgery in the Harris score < 80 group were remarkably increased compared with Harris score ≥ 80 group ( P < .05). In addition, we found that the serum HMGB1 levels in Harris score < 80 group were markedly elevated than the patients in Harris score ≥ 80 group at all time points ( P < .05). The results showed that the serum HMGB1 levels at postoperative 48 hours had the highest predictive value for predicting poor prognosis in intertrochanteric fracture patients. It was found that HMGB1, age and VAS after 72 hours of surgery were the risk factors for poor prognosis of intertrochanteric fracture patients. Conclusion: This study showed that the serum HMGB1 levels was significantly decreased in intertrochanteric fracture patients with bad prognoses. This study may provide a new approach to screening intertrochanteric fracture patients with worse prognoses in advance.